Online art therapy pilot in the Western Isles of Scotland: a feasibility and acceptability study of a novel service in a rural community - Zubala, Ania; Kennell, Nicola; MacInnes, Catriona; MacInnes, Marion; Malcolm, Martin (Frontiers in Psychiatry, 2023)
Introduction Art therapy, despite being an evidence-based, safe and acceptable intervention, is not widely available to clients in Scotland. Online delivery has the potential to expand the reach and accessibility, but special considerations need to be given to designing successful online art therapy services, due to the unique emphasis on the role of an image and artmaking alongside the therapeutic relationship. Methods A pilot online art therapy service was developed and delivered in the Western Isles of Scotland to individual adult clients wishing to increase their psychological wellbeing. This research aimed to assess feasibility and acceptability of the novel service, identify enablers and challenges in setting up and delivering the service, explore participants’ expectations and experiences of art therapy and identify any impacts of the service. Mixed-method evaluation incorporated questionnaires, focus groups, interviews and Audio Image Recordings (AIRs). Findings were grouped into themes across several key areas: service setup, research procedures, intervention design and impacts and insights. Recommendations were developed for the first three areas and the last section presents indications of change and gives voice to client experience primarily. Results Online art therapy was described by clients as a judgement-free zone which allowed freedom to experiment, express, feel and immerse themselves in the creative flow. Other benefits included readiness to accept emotions, increased understanding of self and others and being able to see things from a new perspective. Clients recognised the unique nature of art therapy in relation to other psychological treatments and valued the freedom of expression it offered, including the non-verbal. Discussion This project demonstrated that online art therapy is not only a feasible an acceptable intervention, but potentially also a powerfully impactful one, capable of instilling a positive change in a surprisingly short period of time. Exploring ways to expand current and introduce new art therapy services is highly recommended. Refinement of an intervention design, tools and research procedures is recommended through further feasibility studies of a larger scale.